On-site comparison of an enzymatic detergent and a non-enzymatic detergent-disinfectant for routine manual cleaning of flexible endoscopes - Gonzalez, Jonathan Alfageme (Endosc Int Open, 2019)
Background and study aims  Flexible endoscopes are potential vectors of pathogen transmission to patients that are subjected to cleaning and high-level disinfection after each procedure. Efficient manual cleaning is a prerequisite for effective high-level disinfection. The goal of this study was to demonstrate the impact of the cleaning chemistry in the outcome of the manual cleaning of endoscopes. Materials and methods  Twelve endoscopes were included in this study: four colonoscopes, four gastroscopes, two duodenoscopes and two bronchoscopes. This study was designed with two phases; in each of them, the manual cleaning procedure remained identical, but a different detergent was used: a non-enzymatic detergent-disinfectant (NEDD) and an enzymatic detergent (ED). Biopsy and suction channels of endoscopes were sampled using 10 mL of physiological saline at two points: before and after manual cleaning, and adenosine triphosphate (ATP) was measured on each sample. In total, 208 procedures were analyzed for the NEDD phase and 253 for the ED phase. Results  For each endoscope type, cleaning endoscopes with ED resulted in larger median decrease in ATP than with NEDD: respectively 99.43 % and 95.95 % for bronchoscopes ( P  = 0.0007), 99.28 % and 96.93 % for colonoscopes ( P  < 0.0001) and 98.36 % and 95.36 % for gastroscopes ( P  < 0.0001). In addition, acceptability rates of endoscopes based on defined post-manual cleaning ATP thresholds (200, 150, 100 or 50 relative light units) for all endoscope types were significantly higher with ED compared to NEDD. Conclusions  With all other parameters of manual cleaning remaining unchanged, the enzymatic chemistry of ED provided more consistent and improved cleaning of endoscopes compared to NEDD. Therefore, choice of the detergent for endoscope cleaning has an impact on the outcome of this process.